2021
DOI: 10.1128/jb.00213-21
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an α-Glucosidase Enzyme Conserved in Gardnerella spp. Isolated from the Human Vaginal Microbiome

Abstract: Gardnerella spp. in the vaginal microbiome are associated with bacterial vaginosis, in which a lactobacilli dominant community is replaced with mixed bacteria including Gardnerella species. Co-occurrence of multiple Gardnerella species in the vaginal environment is common, but different species are dominant in different women. Competition for nutrients, including glycogen, could play an important role in determining the microbial community structure. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…1A ). This intracellular α-glucosidase has been previously shown to hydrolyze α-1,4 glycosidic bonds of malto-oligosaccharides to release glucose ( 20 ) while pullulanase is a debranching enzyme that breaks down α-1,6 glycosidic bonds ( 21 ). Thus, the MalXFGK operon encodes all of the components needed to import malto-oligosaccharides and/or maltodextrins for debranching and hydrolysis by pullulanase and α-glucosidase to release glucose.…”
Section: Discussionmentioning
confidence: 99%
“…1A ). This intracellular α-glucosidase has been previously shown to hydrolyze α-1,4 glycosidic bonds of malto-oligosaccharides to release glucose ( 20 ) while pullulanase is a debranching enzyme that breaks down α-1,6 glycosidic bonds ( 21 ). Thus, the MalXFGK operon encodes all of the components needed to import malto-oligosaccharides and/or maltodextrins for debranching and hydrolysis by pullulanase and α-glucosidase to release glucose.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Gardnerella spp. have conserved intracellular α-glucosidase that can release glucose from smaller oligosaccharides (47).…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms of extracellular glycogen utilization in Gardnerella spp. Glycogen is digested into malto-oligosaccharides by α-amylase-pullulanase and α-amylase and these breakdown products are transported inside and can be further digested to glucose by other glycosyl hydrolases including a previously characterized α-glucosidase enzyme (47). Extracellular glycogen breakdown products can also be utilized by other resident microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In Gardnerella , the MalXFGK operon also encodes an α -glucosidase and a pullulanase (Figure 1A). This intracellular α -glucosidase has been previously shown to hydrolyze α -1,4 glycosidic bonds of malto-oligosaccharides to release glucose (28) while pullulanase is a debranching enzyme that breaks down α -1,6 glycosidic bonds (29). Thus the MalXFGK operon encodes all of the components needed to import malto-oligosaccharides and/or maltodextrins for debranching and hydrolysis by pullulanase and α -glucosidase to release glucose.…”
Section: Discussionmentioning
confidence: 99%